Tlingit house, Sitka, Alaska, June 1906. - Cobb, John N.
Front of house with thunderbird design painted on front at top, clothes hanging on line in foreground. Note from Cobb field notebook: Indian house, Sitka, Alaska. Note from unidentified source: With painted Thunderbird design on front.